Cytokine Levels and Human Herpesviruses in Saliva from Clinical Periodontal Healthy Subjects with Peri-Implantitis: A Case-Control Study - Marques Filho, Jaime S.; Gobara, Jorge; da Silva Salomao, Gustavo Vargas; Sumita, Laura M.; Shibli, Jamil A.; Viana, Renato G.; Schwartz Filho, Humberto O.; Pannuti, Claudio Sergio; Braz-Silva, Paulo Henrique; Pallos, Debora (Mediators of Inflammation, 2018)
This study evaluated the presence of cytokines (IL-1β, IL-2, IL-4, IL-6, MCP-1, MIP-1α, MIP-1β, and TNF-α) and human herpesvirus (HSV1, HSV2, EBV, CMV, VZV, HHV6, HHV7, and HHV8) in saliva samples taken from subjects with and without peri-implantitis. Forty-two periodontally healthy subjects were divided according to peri-implant condition: healthy and peri-implantitis groups. The clinical parameters as probing depth, clinical attachment level, plaque index, gingival bleeding, bleeding on probing, and suppuration were evaluated. For cytokine detection, multiplex analysis was performed, and PCR assay was used to identify herpesviruses. No significant differences were found in cytokine levels between groups (p>0.05). The presence of herpesvirus was 1.97-fold higher in patients with peri-implantitis (odds ratio, CI 0.52–7.49). The association of the presence or absence of herpesvirus with the salivary markers was statistically significant for MIP-1β (p=0.0087) and TNF-α (p=0.0437) only in the peri-implantitis group. The presence of herpesviruses in patients with peri-implantitis suggests the development of a proinflammatory environment, which is characterized by increased expression of MIP-1β and TNF-α in saliva.